COOPERATIVE LEARNING AND BREAKOUT ROOMS IN ONLINE CLASSROOMS: INCREASING STUDENT ENGAGEMENT AND DEVELOPING CREATIVITY - Dr. Anuradha Sekhri; Kuljinder Kaur (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Creativity plays an important part in innovation and invention and is important in professions such as business, economics, architecture, mathematics, music, science, and engineering and teaching. Cooperative learning can be defined as a range of concepts and techniques for enhancing the value of student-student interaction. The article begins with separate discussions of how cooperative learning promotes effective instruction of thinking skills and creativity, and of information technology. Thinking skills and creativity are promoted when students interact with their peers to brainstorm, explain, question, disagree, persuade, and problem-solve. Cooperative learning offers many tools for structuring this type of thinking interaction. Teachers can and should begin early in the school year facilitating discussions with students about cooperative learning alongside its use. Teachers may find that some students express a desire for a more heavy-handed lead from the teacher, consistent with their previous experiences. However, these early discussions offer an opportunity for students to learn how their input influences the practices of the classroom community and their co-regulated and self-regulated learning.